Serum Selenium Status as a Diagnostic Marker for the Prognosis of Liver Transplantation - Gül-Klein, Safak; Haxhiraj, Deana; Seelig, Julian; Kästner, Anika; Hackler, Julian; Sun, Qian; Heller, Raban Arved; Lachmann, Nils; Pratschke, Johann; Schmelzle, Moritz; Schomburg, Lutz (Nutrients, 2021)
The trace element selenium (Se) is taken up from the diet and is metabolized mainly by hepatocytes. Selenoprotein P (SELENOP) constitutes the liver-derived Se transporter. Biosynthesis of extracellular glutathione peroxidase (GPx3) in kidney depends on SELENOP-mediated Se supply. We hypothesized that peri-operative Se status may serve as a useful prognostic marker for the outcome in patients undergoing liver transplantation due to hepatocellular carcinoma. Serum samples from liver cancer patients were routinely collected before and after transplantation. Concentrations of serum SELENOP and total Se as well as GPx3 activity were determined by standardized tests and related to survival, etiology of cirrhosis/carcinoma, preoperative neutrophiles, lymphocytes, thyrotropin (TSH) and Child–Pugh and Model for End-Stage Liver Disease (MELD) scores. A total of 221 serum samples from 79 transplanted patients were available for analysis. The Se and SELENOP concentrations were on average below the reference ranges of healthy subjects. Patients with ethanol toxicity-dependent etiology showed particularly low SELENOP and Se concentrations and GPx3 activity. Longitudinal analysis indicated declining Se concentrations in non-survivors. We conclude that severe liver disease necessitating organ replacement is characterized by a pronounced Se deficit before, during and after transplantation. A recovering Se status after surgery is associated with positive prognosis, and an adjuvant Se supplementation may, thus, support convalescence.